Social touch, social isolation, and loneliness in borderline personality disorder during the COVID-19 pandemic - Schulze, Anna; Biermann, Miriam; Atanasova, Konstantina; Unterseher, Franziska; Winkler, Louisa; Bohus, Martin; Lis, Stefanie (Frontiers in psychiatry, 2022)
BackgroundInterpersonal impairments in borderline personality disorder (BPD) are characterised by a lack in the sense of belonging and the fear of being excluded. One feature of interactions that can promote a sense of social belonging is interpersonal touch. While some studies suggest that individuals with BPD experience social touch as less pleasurable than healthy individuals (HCs), there are no studies that investigated whether this difference is associated with feeling less socially connected. This question is particularly important during the COVID-19 pandemic, since one central behavioural recommendation is “social distancing”. An increase in loneliness has been discussed as a consequence and it has been suggested that individuals with BPD may be particularly burdened. However, the primary goal of “social distancing” is not preventing social contacts, but physical proximity. In our study we investigated the interplay between feeling close to others, contact frequency and the appraisal of social touch in BPD. We were additionally interested in whether these factors contribute to the burden through “physical distancing”.MethodsWe assessed subjective and objective social isolation, the need, importance, and liking of social touch, as well as the burden through “physical distancing” policies in 130 women (61 BPD and 69 HCs).ResultsParticipants of the BPD group reported higher loneliness, less social contacts and a lower need for, importance and liking of social touch compared to HCs. Larger social networks, higher frequency of in-person contacts and higher liking and importance of social touch were associated with lower levels of loneliness. Both groups did not differ regarding their burden through “physical distancing”. A higher need for and lower importance of social touch predicted a higher burden through “physical distancing”.ConclusionsA positive appraisal of social touch was associated with less loneliness, independently of an individual's objective social isolation. In BPD, impairments of this fundamental facet of social interaction might hamper forming and strengthening of social bonds and contribute to the patients' interpersonal dysfunction. Changing the attitude towards social touch and in consequence its liking and importance in social interaction might provide one avenue to improve the sense of social connectedness in these patients.
Gesehen am 04.11.2022